EFFECT OF PROBIOTIC Lactococcus plantarum FROM BLONDO ON THE FEED INTAKE AND FEED CONVERSION OF LAYING HENS - Risna, Yayuk Kurnia (JURNAL LENTERA, 2013)
The study was conducted to determine the use of Lactococcus plantarum as a probiotic onperformance and egg quality. This study used 150 individual layers of medium type strain of IsaBrown age 20 weeks. The study consisted of 5 treatments and each treatment was divided into 3replications, each replication consisting of 8 treatment tails, 1 head and 1 tail cut reserves for LacticAcid Bacteria (LAB) in the small intestine and distributed randomly. Treatment A is the controltreatment (placebo / no provision of probiotic Lactococcus plantarum), treatment B (1 mlLactococcus plantarum), treatment C (2 ml Lactococcus plantarum), treatment D (3 ml Lactococcusplantarum) and treatment E (probiotic commercial). Lactococcus plantarum probiotic treatment wasadministered orally to chickens. Feed given 3 times a day and drinking water given adlibitum for 12weeks research. The treatment had no effect on feed intake (P> 0.05) and yolk color but weresignificantly different (P <0.01) daily egg production, egg weight, egg mass, feed conversion, eggcholesterol, Haugh unit, thick shell eggs and the population of LAB in the small intestine. Researchshows Lactococcus plantarum probiotic administration with a level of 2 ml is able to improveperformances of chicken (feed intake: 101.14 g/hen/day, feed conversion: 2.55).Keywords: probiotics, Lactococcus plantarum, LAB, feed intake, feed conversion, layinghens